2018
DOI: 10.1103/physreve.97.022614
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic aggregation with vertically inverted systems

Abstract: Flow patterns surrounding particles suspended near electrodes within an electrolyte solution can be induced with an electric field due to an electrohydrodynamic (EHD) force. Depending on electrolyte, particle, and field properties, a variety of particle packing and stability states have been observed in EHD flow. In this work, we report evidence of EHD flow-induced aggregation of 2-μm sulfonated latex beads in NaCl and NaOH electrolyte solutions, in inverted particle-electrode orientations. Experimental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Finally, consistent with the predicted voltage dependency, the magnitude of the experimentally applied potential was observed to have a weak effect above a threshold voltage. The previously proposed EHD flow mechanism for particle height bifurcation , fails to capture these observed dependencies and is unable to account for the extreme levitation heights measured experimentally.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Finally, consistent with the predicted voltage dependency, the magnitude of the experimentally applied potential was observed to have a weak effect above a threshold voltage. The previously proposed EHD flow mechanism for particle height bifurcation , fails to capture these observed dependencies and is unable to account for the extreme levitation heights measured experimentally.…”
Section: Discussionmentioning
confidence: 84%
“…These results suggested that the key role of the surrounding electrolyte is to set the magnitude of the critical frequency (∼25 Hz in 1 mM NaOH) at which particles transition between separating and aggregating behaviors. The existence of a critical aggregation frequency has since been corroborated by Ruud and Dutcher who also showed that particles “levitated” away from the upper electrode as well to a stable height some distance beneath it. It should be noted that below the critical frequency, particles levitated out of the visible focal plane to extreme distances above the electrode .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…To handle fluidic samples of low particle density, a concentration procedure is usually inevitable to confine the sample volume to an effective working range (nanoliter to microliter) that microfluidic devices can handle . For such, a number of microfluidic particle manipulation methods, such as hydrodynamics , ultrasonics , magnetism , concentration polarization , CE , electrohydrodynamics (EHD) , and dielectrophoresis (DEP) , have been studied in‐depth.…”
Section: Introductionmentioning
confidence: 99%